Pengaruh Bambu Untuk Pipa Distribusi Air Minum Terhadap Kualitas Air (Studi Kasus Distribusi Air Minum Di Paweden, Karangkobar, Banjarnegara) - Nastain Nastain; Gito Sugiyanto; Purwanto Bekti Santoso (Dinamika Rekayasa, 2005)
This research was aimed to know bamboo influence to the physical, and chemical characteristic, and water quality. Parameters observed are temperature, color, taste, odor, pH,DO (dissolved oxygen), BOD (biochemical oxygen demand) and COD (biochemical oxygen demand). The result showed that bamboo influence to the physical and chemical characteristic is smaller effect, except to the DO and COD parameters, it is polynomial change. The result of water quality showed that water to bamboo distribution is suitable used to drinking water resources.